2021
DOI: 10.1002/admi.202002240
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spontaneous Oxidative Conversion on the Characteristics of Lead‐Free Halide Perovskite CsSn(IxBr1−x)3 and on the Performance of Perovskite Light‐Emitting Diodes

Abstract: In this study, lead‐free perovskite CsSn(IxBr1−x)3 films with photoluminescence emission wavelengths from 677 to 887 nm are prepared. The influence of air exposure on their characteristics is also investigated. It is found that CsSnI3 can be transformed to Cs2SnI6 upon increasing the air exposure time. The decomposition and oxidation mechanisms are confirmed by the X‐ray diffraction pattern due to the presence of CsI peak. It is observed that devices based on the CsSn(IxBr1−x)3 film with increased Br− ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Interestingly, by exposing the single ABX 3 perovskite CsSnI 3 to air, it can transform to the vacancy ordered Cs 2 SnI 6 state by the oxidation of Sn 2+ to Sn 4+ . 54 Compared to the conventional ABX 3 , A 2 BX 6 compounds typically possess longer B-X bonds, lower defect density, and better stability under ambient conditions. Despite being made by structurally isolated BX 6 octahedra, therefore, exhibiting low structural and electronic dimensionality, some of the materials have surprisingly dispersive electronic bands and low electronic bandgaps.…”
Section: Types Of Lead-free Perovskitesmentioning
confidence: 99%
“…Interestingly, by exposing the single ABX 3 perovskite CsSnI 3 to air, it can transform to the vacancy ordered Cs 2 SnI 6 state by the oxidation of Sn 2+ to Sn 4+ . 54 Compared to the conventional ABX 3 , A 2 BX 6 compounds typically possess longer B-X bonds, lower defect density, and better stability under ambient conditions. Despite being made by structurally isolated BX 6 octahedra, therefore, exhibiting low structural and electronic dimensionality, some of the materials have surprisingly dispersive electronic bands and low electronic bandgaps.…”
Section: Types Of Lead-free Perovskitesmentioning
confidence: 99%
“…In addition, devices based on CsSnI 3 film with longer air exposure time also showed the poor performance with the transforming from CsSnI 3 to Cs 2 SnI 6 , indicating that Sn 2+ were oxidized to Sn 4+ (Figure 4a). [80] Aside from Hong and co-workers first reported PeLEDs made from all-inorganic Sn-based perovskite materials, organic-inorganic hybrid perovskite materials based on Sn were also investigated almost at the same time. Lai et al demonstrated tunable NIR PeLEDs based on CH 3 NH 3 SnI 3 .…”
Section: Sn-based Peledsmentioning
confidence: 99%
“…With an inverted LED structure of ZnO nanocrystal/polyethylenimine (PEI) bilayer as an electron-transporting layer (ETL), a (OAm) 2 SnBr 4 2D perovskite film as an emitting layer, 4,4,4″-tris(carbazol-9-yl) triphenylamine (TCTA) as a hole-transporting layer (HTL), and MoO 3 /Au as an anode, the devices based on (OAm) 2 SnBr 4 2D perovskite obtained a low turn-on voltage of 2.2 V, a maximum luminance of 350 cd m −2 and a maximum EQE of 0.1%. [56] By further investigating the main problems of the 2D Sn-based [80] Copyright 2021, Wiley-VCH. b) General crystal schematic of a (PEA) 2 SnI x Br 4−x perovskite (light gray balls: NH 3+ groups; red polyhedra: corner-sharing SnX 6 4− octahedra, where X represents a halide) with alternating organic-inorganic layers.…”
Section: Sn-based Peledsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the higher hole injection barrier and/or trap densities for high bromide ratio compositions in the Sn-based PeLEDs. [27] We further measured the EL spectra and operation stability for Pb-and Sn-based PeLEDs. Figure 4D shows the EL spectra of the PeLEDs under an applied voltage of 4 V at different time intervals.…”
Section: Forschungsartikelmentioning
confidence: 99%